Thermoplastic resin composition and molded article thereof

The thermoplastic resin composition with acrylate-aromatic vinyl compound-vinyl cyanide graft copolymers, polymethacrylate, and polyamide addresses the limitations of ASA resins by enhancing weather resistance and surface texture, maintaining mechanical properties, and providing a soft, low-gloss finish.

JP7600115B2Active Publication Date: 2024-12-16LG CHEM LTD
View PDF 4 Cites 0 Cited by

Patent Information

Application Number
JP2021535152
Authority / Receiving Office
JP · JP
Patent Type
Patents
Current Assignee / Owner
Priority Date
2020-08-24
Filing Date
2020-08-25
Publication Date
2024-12-16
Estimated Expiration
2040-08-25

AI Technical Summary

Technical Problem

Existing ASA resins used in exterior materials face limitations in improving weather resistance and surface texture while maintaining low gloss and mechanical properties.

Method used

A thermoplastic resin composition comprising specific ratios of acrylate-aromatic vinyl compound-vinyl cyanide graft copolymers, polymethacrylate, and polyamide, which enhance weather resistance and reduce surface roughness while maintaining mechanical properties and processability.

Benefits of technology

The composition achieves improved weather resistance, low surface roughness, and uniform gloss, providing a sensually soft feel compared to conventional ASA resins.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure 0007600115000001
    Figure 0007600115000001
  • Figure 0007600115000002
    Figure 0007600115000002
Patent Text Reader

Abstract

The present invention relates to a thermoplastic resin composition and a molded article thereof, and more specifically to a thermoplastic resin composition and a molded article thereof, characterized by comprising: A-1) 10 to 30% by weight of an acrylate-aromatic vinyl compound-vinyl cyanide compound graft copolymer containing an acrylate rubber having an average particle size of 0.05 to 0.15 μm; A-2) 20 to 40% by weight of an acrylate-aromatic vinyl compound-vinyl cyanide compound graft copolymer containing an acrylate rubber having an average particle size of 0.3 to 0.5 μm; B) 0 to 35% by weight of an aromatic vinyl polymer; and C) 10 to 60% by weight of a polymethacrylate; and D) 0.5 to 10 parts by weight of a polyamide. According to the present invention, it is possible to provide a low-gloss thermoplastic resin composition and a molded article thereof, which have mechanical properties and processability equivalent to or better than those of conventional ASA-based resins, excellent weather resistance, a low surface roughness value that gives a soft feel, and a uniform surface gloss.
Need to check novelty before this filing date? Find Prior Art

Description

[Technical field]

[0001] CROSS-REFERENCE TO RELATED APPLICATIONS This application claims the benefit of priority based on Korean Patent Application No. 10-2019-0110417 filed on September 6, 2019 and Korean Patent Application No. 10-2020-0106135 refiled on August 24, 2020, and all contents disclosed in the documents of said Korean patent application are incorporated by reference as part of this specification.

[0002] The present invention relates to a thermoplastic resin composition and a molded article thereof, and more particularly to a low-gloss thermoplastic resin composition and a molded article thereof, which have mechanical properties and processability equivalent to or greater than those of conventional ASA-based resins, excellent weather resistance, a low surface roughness value that gives a soft feel, and a uniform surface gloss. [Background technology]

[0003] Acrylate compound-styrene-acrylonitrile copolymer (hereinafter referred to as "ASA resin") has weather resistance, aging resistance, chemical resistance, rigidity, impact resistance and processability, and has a wide range of uses, so it is widely used in the fields of automobiles, miscellaneous goods, and building materials.

[0004] However, in the case of ASA resins in the field of exterior materials, there is an increasing need to develop low-gloss ASA resins that can meet the needs for aesthetic resins that are free from the artificial feel of plastic.

[0005] Although low gloss was achieved by using crystalline resins such as nylon as the low gloss ASA resin, there was a limit to the improvement of weather resistance and surface texture, which are physical properties that are just as important for exterior materials as low gloss. [Prior art documents] [Patent documents]

[0006] [Patent Document 1] Korean Patent Publication No. 10-2009-0095764 Summary of the Invention [Problem to be solved by the invention]

[0007] In order to solve the above-mentioned problems of the conventional technology, the present invention aims to provide a low-gloss thermoplastic resin composition and a molded article thereof, which have mechanical properties and processability equivalent to or better than those of conventional ASA-based resins, excellent weather resistance, a low surface roughness value that gives a soft feeling, and a uniform surface gloss.

[0008] The above and other objects of the present invention can be achieved by the present invention described below. [Means for solving the problem]

[0009] In order to achieve the above object, the present invention provides a thermoplastic resin composition and a molded article thereof, characterized by comprising: A-1) 10 to 30% by weight of an acrylate-aromatic vinyl compound-vinyl cyanide compound graft copolymer containing an acrylate rubber having an average particle size of 0.05 to 0.15 μm; A-2) 20 to 40% by weight of an acrylate-aromatic vinyl compound-vinyl cyanide compound graft copolymer containing an acrylate rubber having an average particle size of 0.3 to 0.5 μm; B) 0 to 35% by weight of an aromatic vinyl polymer; and C) 100 parts by weight of a base resin consisting of 10 to 60% by weight of a polymethacrylate; and D) 0.5 to 10 parts by weight of a polyamide. Effect of the Invention

[0010] According to the present invention, there is provided a low-gloss thermoplastic resin composition and a molded article thereof, which have mechanical properties and processability equivalent to or greater than those of conventional ASA-based resins, excellent weather resistance, a low surface roughness value that gives a soft feel, and a uniform surface gloss. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS

[0011] The thermoplastic resin composition and molded articles thereof according to the present invention will be described in detail below.

[0012] The present inventors have confirmed that, when trying to realize a fading effect by adding polyamide to an ASA resin, by adjusting the morphology of the ASA resin and including a methyl methacrylate-styrene-acrylonitrile copolymer or polymethyl methacrylate as an essential component in a specific composition ratio, a low gloss thermoplastic resin composition can be obtained that has mechanical properties and processability equivalent to or greater than those of conventional ASA-based resins, has improved weather resistance, and has a lower surface roughness, making it soft to the touch and has a uniform surface gloss. Based on this, the present inventors have further pursued research and completed the present invention.

[0013] The thermoplastic resin composition of the present invention is characterized by comprising: A-1) 10-30% by weight of an acrylate-aromatic vinyl compound-vinyl cyanide compound graft copolymer containing an acrylate rubber having an average particle diameter of 0.05-0.15 μm; A-2) 20-40% by weight of an acrylate-aromatic vinyl compound-vinyl cyanide compound graft copolymer containing an acrylate rubber having an average particle diameter of 0.3-0.5 μm; B) 0-35% by weight of an aromatic vinyl polymer; and C) 10-60% by weight of a base resin; and D) 0.5-10 parts by weight of a polyamide. In this case, the thermoplastic resin composition has the advantage of providing a thermoplastic resin composition that has excellent weather resistance, low gloss, uniform surface gloss, and low surface roughness, while maintaining mechanical properties and processability at the same level or higher than those of conventional ASA-based resins, and thus gives a soft feeling.

[0014] Each component constituting the thermoplastic resin composition of the present invention will be described in detail below.

[0015] A-1) Acrylate-aromatic vinyl compound-vinyl cyanide compound graft copolymer The acrylate rubber of the A-1) graft copolymer may have, for example, an average particle size of 0.05 to 0.15 μm, preferably 0.1 to 0.15 μm, more preferably 0.12 to 0.15 μm, and even more preferably 0.12 to 0.14 μm or 0.13 to 0.15 μm. Within this range, the finally produced thermoplastic resin composition can be imparted with excellent weather resistance, colorability, impact strength, chemical resistance and surface gloss properties.

[0016] The acrylate rubber may preferably be the core.

[0017] In this description, the average particle size can be measured using dynamic light scattering, specifically, using a Nicomp380 instrument (product name, manufacturer: PSS).

[0018] In the present description, the average particle size can mean the arithmetic average particle size in the particle size distribution measured by dynamic light scattering, specifically the scattering intensity average particle size.

[0019] The A-1) graft copolymer is, for example, 10 to 30% by weight, preferably 15 to 25% by weight, and more preferably 15 to 20% by weight. Within this range, the effect of excellent weather resistance, fluidity, tensile strength, and impact strength is achieved.

[0020] The A-1) graft copolymer may, for example, contain 40 to 60% by weight of an acrylate rubber, 25 to 45% by weight of an aromatic vinyl compound, and 10 to 20% by weight of a vinyl cyanide compound. Within these ranges, the copolymer has excellent weather resistance, fluidity, tensile strength, and impact strength.

[0021] As a preferred example, the A-1) graft copolymer may contain 45 to 55% by weight of an acrylate rubber, 30 to 50% by weight of an aromatic vinyl compound, and 5 to 20% by weight of a vinyl cyanide compound. Within these ranges, the copolymer has excellent weather resistance, fluidity, tensile strength, and impact strength.

[0022] As a more preferred example, the A-1) graft copolymer may contain 45 to 55% by weight of an acrylate rubber, 30 to 40% by weight of an aromatic vinyl compound, and 10 to 20% by weight of a vinyl cyanide compound. Within these ranges, the effect of excellent weather resistance, fluidity, tensile strength, and impact strength is obtained.

[0023] In this description, a polymer comprising a certain compound means a polymer polymerized containing that compound, where the units in the polymerized polymer are derived from that compound.

[0024] The A-1) graft copolymer may be prepared, for example, by emulsion polymerization, and in this case, it has the effect of being excellent in chemical resistance, weather resistance, fluidity, tensile strength and impact strength.

[0025] The emulsion polymerization is not particularly limited as long as it is an emulsion graft polymerization method commonly used in the technical field to which the present invention pertains.

[0026] The acrylate may be, for example, one or more selected from the group consisting of alkyl acrylates in which the alkyl group has 2 to 8 carbon atoms, preferably an alkyl acrylate in which the alkyl group has 4 to 8 carbon atoms, and more preferably butyl acrylate or ethylhexyl acrylate.

[0027] The aromatic vinyl compound may be, for example, one or more selected from the group consisting of styrene, α-methylstyrene, m-methylstyrene, p-methylstyrene, and p-tert-butylstyrene, and is preferably styrene.

[0028] The vinyl cyanide compound may be, for example, one or more selected from the group consisting of acrylonitrile, methacrylonitrile, ethyl acrylonitrile, and isopropyl acrylonitrile, and is preferably acrylonitrile.

[0029] A-2) Acrylate-aromatic vinyl compound-vinyl cyanide compound graft copolymer The acrylate rubber of the A-2) graft copolymer may, for example, have an average particle size of 0.3 to 0.5 μm, preferably 0.35 to 0.5 μm, more preferably 0.4 to 0.5 μm, and even more preferably 0.45 to 0.50 μm. Within this range, the weather resistance is good, while the mechanical strength such as fluidity, tensile strength, and impact strength is excellent.

[0030] The acrylate rubber may preferably be the core.

[0031] The A-2) graft copolymer is, for example, 20 to 40% by weight, preferably 25 to 35% by weight, and more preferably 30 to 35% by weight. Within this range, the weather resistance, fluidity, tensile strength, and impact strength are excellent.

[0032] The A-2) graft copolymer may, for example, contain 40 to 60% by weight of an acrylate rubber, 25 to 45% by weight of an aromatic vinyl compound, and 10 to 20% by weight of a vinyl cyanide compound. Within these ranges, the copolymer has excellent weather resistance, fluidity, tensile strength, and impact strength.

[0033] As a preferred example, the A-2) graft copolymer may contain 45 to 55% by weight of an acrylate rubber, 30 to 40% by weight of an aromatic vinyl compound, and 10 to 20% by weight of a vinyl cyanide compound. Within these ranges, the effect of excellent weather resistance, fluidity, tensile strength, and impact strength is obtained.

[0034] The A-1) graft copolymer may be contained in an amount smaller than that of the A-2) graft copolymer, and more preferably, the weight ratio of the A-1) graft copolymer to the A-2) graft copolymer is 1:1.1 to 1:4, more preferably 1:1.2 to 1:2. Within this range, the effect of excellent weather resistance, fluidity, tensile strength and impact strength is obtained.

[0035] The sum of the weights of the A-1) graft copolymer and A-2) graft copolymer is preferably 40 to 60% by weight, more preferably 45 to 55% by weight, and even more preferably 47 to 53% by weight, relative to the base resin. Within this range, the effect of excellent weather resistance, fluidity, tensile strength, and impact strength is achieved.

[0036] The A-2) graft copolymer may be prepared, for example, by emulsion polymerization, and in this case, it has the effect of being excellent in weather resistance, fluidity, tensile strength and impact strength.

[0037] The emulsion polymerization is not particularly limited as long as it is an emulsion graft polymerization method commonly used in the technical field to which the present invention pertains.

[0038] B) Aromatic vinyl polymer The aromatic vinyl polymer B) may be, for example, 0 to 35% by weight, preferably 10 to 35% by weight, more preferably less than 10% by weight, even more preferably less than 5% by weight, and most preferably not contained at all. Within this range, there are advantages in that the weather resistance is excellent, and in particular the surface roughness value is significantly reduced, resulting in a uniform gloss and a soft feel when touched with the hand.

[0039] The aromatic vinyl polymer B) preferably contains 65 to 80% by weight of an aromatic vinyl compound and 20 to 35% by weight of a vinyl cyanide compound. Within these ranges, the polymer has the effect of exhibiting excellent chemical resistance and impact strength.

[0040] The aromatic vinyl polymer B) has, for example, a weight average molecular weight of 80,000 to 180,000 g / mol, preferably 80,000 to 160,000 g / mol. Within this range, the polymer has the effect of being excellent in tensile strength, impact strength, and the like.

[0041] The aromatic vinyl polymer B) is, for example, an aromatic vinyl compound-vinyl cyan compound copolymer, and preferred examples thereof may be styrene-acrylonitrile copolymer (SAN resin), α-methylstyrene-acrylonitrile copolymer (heat-resistant SAN resin), or a mixture thereof, in which case it has the effect of being excellent in heat resistance, etc.

[0042] The styrene-acrylonitrile copolymer may be preferably 15 to 35% by weight, more preferably 15 to 25% by weight, and within this range, there is an effect of excellent heat resistance and the like.

[0043] The styrene-acrylonitrile copolymer preferably contains 65 to 80% by weight of styrene and 20 to 35% by weight of acrylonitrile, and within this range, the copolymer has the effect of exhibiting excellent processability and impact strength.

[0044] The styrene-acrylonitrile copolymer has, for example, a weight average molecular weight of 100,000 to 180,000 g / mol, preferably 100,000 to 150,000 g / mol, and within this range, it has the effect of being excellent in heat resistance and the like.

[0045] The α-methylstyrene-acrylonitrile copolymer may be preferably 10 to 20% by weight, more preferably 12 to 18% by weight, and within this range, there is an effect of excellent heat resistance and the like.

[0046] The α-methylstyrene-acrylonitrile copolymer preferably contains 70 to 75% by weight of α-methylstyrene and 25 to 30% by weight of acrylonitrile, more preferably contains 60 to 75% by weight of α-methylstyrene, 0 to 10% by weight of styrene and 20 to 30% by weight of acrylonitrile, or may contain 60 to 70% by weight of α-methylstyrene, 0 to 10% by weight of styrene and 25 to 30% by weight of acrylonitrile, and further preferably contains 60 to 75% by weight of α-methylstyrene, 5 to 10% by weight of styrene and 20 to 30% by weight of acrylonitrile, or may contain 60 to 70% by weight of α-methylstyrene, 5 to 10% by weight of styrene and 25 to 30% by weight of acrylonitrile, and within this range, there is an effect of excellent heat resistance, etc.

[0047] The α-methylstyrene-acrylonitrile copolymer preferably has a weight average molecular weight of 80,000 to 120,000 g / mol. Within this range, the copolymer has the effect of being excellent in heat resistance and the like.

[0048] In this description, unless otherwise specified, the weight average molecular weight can be measured using GPC (gel permeation chromatography, water breeze), specifically, using THF (tetrahydrofuran) as an eluent via GPC (gel permeation chromatography, water breeze) as a relative value to a standard PS (standard polystyrene) sample.

[0049] The aromatic vinyl polymer B may be produced by, for example, suspension polymerization, emulsion polymerization, solution polymerization or bulk polymerization, and in this case, it has the effect of being excellent in heat resistance and fluidity.

[0050] The suspension polymerization, emulsion polymerization, solution polymerization and bulk polymerization are not particularly limited as long as they are solution polymerization and bulk polymerization methods commonly used in the technical field to which the present invention pertains.

[0051] C) Polymethacrylate The C) polymethacrylate may be, for example, 10 to 60% by weight, preferably 25 to 55% by weight, more preferably 25 to 50% by weight, even more preferably 30 to 50% by weight, even more preferably 35 to 50% by weight, and most preferably 45 to 50% by weight. Within this range, compared to conventional ASA-based resins, mechanical properties and processability are maintained at the same level or higher, while weather resistance is greatly improved and the surface roughness is very low, resulting in a soft feel.

[0052] The C) polymethacrylate preferably contains 55% by weight or more of methacrylate monomer, more preferably 60% by weight or more, and most preferably 65% ​​by weight or more. Within this range, the weather resistance is greatly improved and the surface roughness is very low, resulting in a soft feel.

[0053] The methacrylate monomer may be, for example, an alkyl methacrylate having an alkyl group with 1 to 15 carbon atoms, and specifically may be one or more selected from the group consisting of methyl methacrylate, ethyl methacrylate, butyl methacrylate, 2-ethylbutyl methacrylate, 2-ethylhexyl methacrylate, and lauryl methacrylate, and may preferably be an alkyl methacrylate containing a chain alkyl group with 1 to 4 carbon atoms, and more preferably may be methyl methacrylate.

[0054] The C) polymethacrylate is preferably at least one selected from the group consisting of polymethyl methacrylate resin and methyl methacrylate-styrene-acrylonitrile copolymer, more preferably polymethyl methacrylate resin or methyl methacrylate-styrene-acrylonitrile copolymer, and even more preferably polymethyl methacrylate resin. Within this range, there is an effect of being more excellent in weather resistance and having a low surface roughness value, resulting in a soft feel.

[0055] The polymethyl methacrylate resin may have a weight average molecular weight of, for example, 35,000 to 200,000 g / mol, and preferably 50,000 to 200,000 g / mol. Within this range, the resin has excellent weather resistance, excellent fluidity, tensile strength and impact strength, and a low surface roughness value, resulting in a soft feel.

[0056] As another example, the polymethyl methacrylate resin may be a mixture of a polymethyl methacrylate resin having a weight average molecular weight of 50,000 to 200,000 g / mol (hereinafter referred to as a "high molecular weight PMMA resin") and a polymethyl methacrylate resin having a weight average molecular weight of 35,000 to 45,000 g / mol (hereinafter referred to as a "low molecular weight PMMA resin").

[0057] The high molecular weight PMMA resin and the low molecular weight PMMA resin may have a weight ratio of, for example, 1:0.1 to 2.0, preferably 1:1.3 to 1.7, and more preferably 1:1.4 to 1.6. Within this range, the resin has excellent fluidity, tensile strength, and impact strength, and has even better weather resistance. The resin also has a low surface roughness, which gives the resin a soft feel.

[0058] In this description, the weight ratio of A to B means the weight ratio of A:B.

[0059] The methyl methacrylate-styrene-acrylonitrile copolymer, for example, contains 65 to 85% by weight of methyl methacrylate, 5 to 30% by weight of styrene, and 5 to 10% by weight of acrylonitrile. Within these ranges, the weather resistance is excellent and the surface roughness is low, resulting in a soft feel.

[0060] The methyl methacrylate-styrene-acrylonitrile copolymer may have a weight average molecular weight of, for example, 70,000 to 140,000 g / mol, or, for example, 70,000 to 90,000 g / mol, or more than 90,000 g / mol to 140,000 g / mol or less. Within this range, the copolymer has the effects of being more excellent in weather resistance, fluidity, tensile strength, and impact strength, and has a low surface roughness value, resulting in a soft feel.

[0061] As another example, the methyl methacrylate-styrene-acrylonitrile copolymer may be a mixture of a methyl methacrylate-styrene-acrylonitrile copolymer having a weight average molecular weight of 70,000 to 90,000 g / mol (hereinafter referred to as a "low molecular weight SAMMA resin") and a methyl methacrylate-styrene-acrylonitrile copolymer having a weight average molecular weight of 120,000 to 140,000 g / mol (hereinafter referred to as a "high molecular weight SAMMA resin").

[0062] For example, the weight ratio of the low molecular weight SAMMA resin to the high molecular weight SAMMA resin may be 1:0.1 to 0.45, preferably 1:0.2 to 0.45, more preferably 1:0.3 to 0.45, and even more preferably 1:0.35 to 0.45. Within this range, there is an advantage in that the resin has excellent weather resistance.

[0063] The C) polymethacrylate may be prepared, for example, by solution polymerization, bulk polymerization, emulsion polymerization, or suspension polymerization. The solution polymerization, bulk polymerization, emulsion polymerization, and suspension polymerization are not particularly limited as long as they are emulsion polymerization and suspension polymerization methods commonly used in the technical field to which the present invention belongs, respectively.

[0064] D) Polyamide The D) polyamide may be, for example, 0.5 to 10 parts by weight, preferably 1 to 8 parts by weight, more preferably 4 to 8 parts by weight, and even more preferably 4 to 6 parts by weight, based on 100 parts by weight of the base resin. Within this range, there are advantages in that the gloss is reduced, the fading effect is large, and the physical properties are well balanced.

[0065] The D) polyamide means a thermoplastic polymer containing an amide bond, and specific examples thereof include polyamide 6, polyamide 66 (PA6.6), polyamide 46, polyamide ll, polyamide 12, polyamide 610, polyamide 612, polyamide 6 / 66, polyamide 6 / 612, polyamide MXD6, polyamide 6 / MXD6, polyamide 66 / MXD6, polyamide 6T, polyamide 6I, polyamide 6 / 6T, polyamide 6 / ... The polyamide may be one or more selected from the group consisting of polyamide 66 / 6T, polyamide 66 / 6I, polyamide 6 / 6T / 6I, polyamide 66 / 6T / 6I, polyamide 9T, polyamide 9I, polyamide 6 / 9T, polyamide 6 / 9I, polyamide 66 / 9T, polyamide 6 / 12 / 9T, polyamide 66 / 12 / 9T, polyamide 6 / 12 / 9I and polyamide 66 / 12 / 6I, and is preferably polyamide 66 (PA6.6).

[0066] The polyamide D) used has, for example, a melting point of 230°C or higher, preferably 240°C or higher, more preferably 250°C or higher, and further preferably 260 to 270°C.

[0067] The polyamide D) used has, for example, a relative viscosity (96% solution in sulfuric acid) of 2.0 to 4.0, preferably 2.0 to 3.5, more preferably 2.0 to 3.0, and further preferably 2.4 to 2.7.

[0068] In this description, the relative viscosity can be measured using an Ubbelohde viscometer according to the ISO 307 sulfuric acid method.

[0069] The method for producing the polyamide D) is not particularly limited as long as it is a polymerization method commonly used in the technical field to which the present invention belongs, and if it meets the definition of the polyamide according to the present invention, it may be commercially purchased and used.

[0070] thermoplastic resin composition As an example, the thermoplastic resin composition described herein may have a surface roughness value, averaged as measured at five locations using an optical profiler system, of 4 or less, preferably 3.5 or less, more preferably 3 or less, and even more preferably 2.5 or less.

[0071] The thermoplastic resin composition may have a weather resistance (ΔE) measured for 2000 hours according to the SAE J1960 method of, for example, 4.0 or less, preferably 3.5 or less, more preferably 3.2 or less, and even more preferably 3.0 or less.

[0072] The thermoplastic resin composition may have a flow index (MI) (220°C, 10 kg load) according to ASTM D1238 of, for example, 3 g / 10 min or more, preferably 7 g / 10 min or more, more preferably 10 g / 10 min or more, and even more preferably 12 g / 10 min or more, and specifically, 12 to 15 g / 10 min.

[0073] The thermoplastic resin composition has, for example, a tensile strength (1 / 8 inch) according to ASTM 638 of 290 kg / cm 2 or more, preferably 380 kg / cm 2 More preferably, it is 400 kg / cm 2 More preferably, it is 470 kg / cm 2 The above is the case, and a specific example is 380 to 490 kg / cm 2 may be also possible.

[0074] The thermoplastic resin composition may have, for example, an Izod impact strength (¼ inch) according to ASTM 256 of 7 kg·cm / cm or more, preferably 9 kg·cm / cm or more, and specifically, 7 to 11 kg·cm / cm or 8 to 11 kg·cm / cm.

[0075] The thermoplastic resin composition has a film gloss (gloss) of 14 or less, 11 or less, or 10.5 or less, preferably 9.5 or less, more preferably 9.3 or less, as an example, 4.8 to 14.0 or 4.8 to 11.0, as measured at 60° using a gloss meter VG7000. Within this range, the thermoplastic resin composition has an effect of having excellent achromatic properties and excellent balance of physical properties. Therefore, the thermoplastic resin composition described in the present invention can also be called an achromatic thermoplastic resin composition.

[0076] The thermoplastic resin composition may further include, as necessary, 0.01 to 5 parts by weight, 0.05 to 3 parts by weight, 0.1 to 2 parts by weight, or 0.5 to 1 part by weight of one or more selected from the group consisting of a heat stabilizer, a light stabilizer, a dye, a pigment, a colorant, a release agent, an antistatic agent, an antibacterial agent, a processing aid, a metal deactivator, a flame retardant, a smoke suppressant, an anti-dripping agent, an anti-friction agent, and an anti-wear agent. Within this range, the inherent physical properties of the thermoplastic resin composition described herein are not deteriorated, and the desired physical properties are effectively realized.

[0077] The method for producing a thermoplastic resin composition of the present invention is characterized by comprising the steps of: A-1) 10-30% by weight of an acrylate-aromatic vinyl compound-vinyl cyanide compound graft copolymer containing an acrylate rubber having an average particle size of 0.05-0.15 μm; A-2) 20-40% by weight of an acrylate-aromatic vinyl compound-vinyl cyanide compound graft copolymer containing an acrylate rubber having an average particle size of 0.3-0.5 μm; B) 0-35% by weight of an aromatic vinyl polymer; and C) 100 parts by weight of a base resin consisting of 10-60% by weight of polymethacrylate; and D) 0.5-10 parts by weight of a polyamide; and then preparing pellets using an extrusion kneader under conditions of 220-280°C. In this case, compared to conventional ASA-based resins, there is an advantage in providing a thermoplastic resin composition that has excellent weather resistance while maintaining mechanical properties and processability at the same level or higher, has low gloss, has uniform surface gloss, and has a low surface roughness value, giving a soft feeling.

[0078] The method for producing the thermoplastic resin composition has all the technical features of the thermoplastic resin composition described above, and therefore, the description of the overlapping parts will be omitted.

[0079] The step of producing pellets using the extrusion kneader can be carried out at preferably 220 to 280° C., more preferably 240 to 280° C., where the temperature means the temperature set in the cylinder.

[0080] The extrusion kneader is not particularly limited as long as it is an extrusion kneader that is commonly used in the technical field to which the present invention pertains, and may be preferably a twin-screw extrusion kneader.

[0081] molded product The molded article of the present invention is characterized by containing the thermoplastic resin composition of the present invention. In this case, compared with conventional molded articles, the molded article has the advantages of excellent weather resistance while maintaining mechanical properties and processability equivalent to or better than those of conventional molded articles, low gloss, uniform surface gloss, and low surface roughness, which gives a soft feel.

[0082] The molded article may be, for example, an extrusion molded article or an injection molded article, and is preferably a building exterior material, and more preferably, siding, a sliding door, or a building fixture.

[0083] The molded article may be preferably produced by a step of extruding or injecting the thermoplastic resin composition described herein at a molding temperature of 190 to 250°C, and has the advantage that an excellent shading effect is exhibited within this range.

[0084] In describing the thermoplastic resin composition, its manufacturing method, and molded products described herein, other conditions, equipment, etc. that are not explicitly described can be appropriately selected within the range commonly used in the art, and it is clearly stated that there are no particular limitations.

[0085] Below, preferred examples are presented to aid in understanding the present invention. However, the following examples are merely illustrative of the present invention, and it will be apparent to those skilled in the art that various changes and modifications are possible within the scope of the scope and technical spirit of the present invention. Naturally, such changes and modifications also fall within the scope of the appended claims.

[0086] [Example] The substances used in the following Examples 1 to 10 and Comparative Examples 1 to 3 are as follows.

[0087] A-1) First graft copolymer by emulsion polymerization (50% by weight of butyl acrylate polymer with an average particle size of 100 nm, shell: 36% by weight of styrene, 14% by weight of acrylonitrile) A-2) Second graft copolymer by emulsion polymerization (50% by weight of butyl acrylate polymer with an average particle size of 400 nm, shell: 38% by weight of styrene, 12% by weight of acrylonitrile) B-1) Bulk polymerization SAN resin (92RF), B-2) Bulk polymerization heat-resistant SAN resin (200UH), C-1) SAMMA resin (XT500) using bulk polymerization method, C-2) Bulk polymerization SAMMA resin (XT510), C-3) PMMA resin (IH830), C-4) PMMA resin (BA611) D) PA6.6

[0088] Examples 1 to 10 and Comparative Examples 1 to 3 The components and contents shown in Table 1 below were mixed and extruded at 280°C in a twin-screw extruder to produce pellets. The melt index of the produced pellets was measured. The produced pellets were also used to produce a 0.15T sheet at a molding temperature of 220°C, and the gloss and surface roughness of the film were measured. The produced pellets were then extruded at a molding temperature of 220°C to produce test pieces for measuring physical properties, which were then used to measure tensile strength and impact strength.

[0089] [Test example] The properties of the pellets, sheets and specimens prepared in Examples 1 to 10 and Comparative Examples 1 to 3 were measured by the following methods, and the results are shown in Table 1 below.

[0090] *Melt index (MI): The produced pellets were measured under the condition of 220°C / 10 kg according to the ASTM D1238 method.

[0091] * Tensile strength (kg / cm 2 ):Measured according to ASTM 638 method.

[0092] *Izod impact strength (kg.cm / cm): Measured according to ASTM 256 method.

[0093] *Film gloss: Measured at 60° using a gloss meter VG7000.

[0094] *Surface roughness value: Average of five measurements taken using an optical profiler system (NV-2700, Nano System Co., Ltd.) under the following conditions: objective lens: 10x x eyepiece: 1x (FOV: 628μm x 471μm), mode: WSI envelope, and scan range: ±30μm. A low surface roughness value means that the surface feels soft to the touch and has a uniform luster.

[0095] *Weather resistance: After measuring for 2000 hours according to the SAE J1960 method, it was evaluated by ΔE calculated by the following formula 1. The lower the ΔE value, the better the weather resistance.

[0096]

number

[0097] [Table 1]

[0098] As shown in Table 1, it was confirmed that the thermoplastic resin compositions according to the present invention (see Examples 1 to 10) have excellent weather resistance while maintaining mechanical properties such as flow index, tensile strength, and impact strength equivalent to or higher than those of Comparative Examples 1 and 2 not containing polymethacrylate resin, have low surface roughness values, give a soft feeling, and have uniform and low surface gloss, compared to Comparative Examples 1 and 2 not containing polymethacrylate resin. In particular, referring to Table 1, in the case of Examples 1 to 3 and Examples 7 to 9 containing 40 to 60 wt%, more specifically 45 to 55 wt%, of polymethacrylate resin, the surface roughness value is 3.0 or less, specifically 2.0 to 3.0, and the weather resistance (△E) is 3.1 or less, specifically 1.3 to 3.3, all of which are very excellent compared to Comparative Examples 1 and 2, and therefore it was confirmed that a thermoplastic resin of high quality was produced.

[0099] On the other hand, in the case of Comparative Example 3 which does not contain polyamide, the gloss is 67, which is at least 6 times and at most 14 times higher than the gloss of Examples 1 to 9. This shows that this is completely inconsistent with the object of the present invention to realize a non-photosensitive property and produce a high-quality photosensitive resin.

Claims

1. A-1) 10 to 30% by weight of an acrylate-aromatic vinyl compound-vinyl cyanide compound graft copolymer containing an acrylate rubber having an average particle size of 0.05 to 0.15 μm, A-2) 20 to 40% by weight of an acrylate-aromatic vinyl compound-vinyl cyanide compound graft copolymer containing an acrylate rubber having an average particle size of 0.3 to 0.5 μm, B) 0% by weight of an aromatic vinyl polymer, and C) 100 parts by weight of a base resin consisting of 30 to 50% by weight of polymethacrylate; D) 0.5 to 10 parts by weight of a polyamide, B) Aromatic vinyl polymers are not included, The polymethacrylate resin C) is a mixture of a polymethyl methacrylate resin having a weight average molecular weight of 50,000 to 200,000 g / mol and a polymethyl methacrylate resin having a weight average molecular weight of 35,000 to 45,000 g / mol; The thermoplastic resin composition has a surface roughness of 2.5 or less, the surface roughness being averaged as measured at five points by an optical profiler system; The thermoplastic resin composition has a weather resistance (ΔE) of 1.8 or less as measured by the SAE J1960 method.

2. The thermoplastic resin composition according to claim 1, characterized in that the thermoplastic resin composition has a non-glossy property in which a film gloss measured at 60° using a gloss meter VG7000 is 14 or less.

3. The thermoplastic resin composition according to claim 1 or 2, characterized in that the A-1) graft copolymer comprises 40 to 60% by weight of an acrylate rubber, 25 to 45% by weight of an aromatic vinyl compound, and 10 to 20% by weight of a vinyl cyan compound.

4. The thermoplastic resin composition according to any one of claims 1 to 3, characterized in that the A-2) graft copolymer comprises 40 to 60% by weight of an acrylate rubber, 25 to 45% by weight of an aromatic vinyl compound, and 10 to 20% by weight of a vinyl cyan compound.

5. The thermoplastic resin composition according to any one of claims 1 to 4, wherein the A-1) graft copolymer is contained in an amount smaller than the A-2) graft copolymer.

6. The sum of the weights of the A-1) graft copolymer and the A-2) graft copolymer is 40 to 60% by weight based on the base resin. The thermoplastic resin composition according to any one of claims 1 to 5.

7. The thermoplastic resin composition according to any one of claims 1 to 6, characterized in that the D) polyamide is polyamide 6.

6.

8. A molded article comprising the thermoplastic resin composition according to any one of claims 1 to 7.

Citation Information

Patent Citations

  • Thermoplastic resin composition

    JP1983222139A

  • Warm bath type thermotherapy device

    JP1998033626A

  • Weatherable styrenic blend with improved translucency

    JP2006509048A

  • Termoplastic resin composition having a good weather resistance and low gloss

    KR1020090095764A